Does E-Government and Control of Corruption Affect Government Effectiveness and Economic Growth in Lower-Middle-Income Countries in Asia? - Jaka Raharja; Eko Priyo Purnomo; Dyah Mutiarin (Fakultas Seni Rupa dan Desain ITB, 2023)
This study examines the impact of e-government and corruption control on government effectiveness and economic growth in lower-middle-income countries in Asia. This study uses SMART PLS to test construct validity, reliability, and discriminant validity to assess data quality. Data is obtained from Worldbank and UN e-government surveys. The results of the study show that e-government has a positive and significant effect on government effectiveness, with a P-value of 0.000 and a T-statistic of 3,664. Control of corruption affects government effectiveness with a P-value of 0.001 and a T-statistic of 3.209; then, government effectiveness has a positive and significant effect on economic growth with a P-value of 0.000 and a T-statistic of 4.026. The findings highlight the importance of adopting efficient e-government practices and effective corruption control measures to improve government performance and promote sustainable economic growth in these countries.